Colorectal Cancer Risk Factors: A Case-Control Study in North of Iran - Ramin Shekarriz; Neshat Roudbari (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Colorectal cancer (CRC) is a significant and costly health issue worldwide, particularly in developing countries like Iran. As the third most common cancer globally, its prevalence varies considerably across different geographical regions and ethnic groups and is closely related to lifestyle factors. Therefore, careful investigations in diverse populations can help improve public health and develop appropriate strategies to reduce the incidence of colorectal cancer. Given the increasing prevalence of this disease, identifying related risk factors in regions with a high prevalence of gastrointestinal cancers, especially in northern Iran, is crucial. This study aims to identify the risk factors associated with colorectal cancer (such as underlying diseases, nutritional habits, and physical activity) in patients referred to the Mazandaran Comprehensive Cancer Center, compared to a control group. Materials and methods: This case-control study included 123 patients with pathology-confirmed colorectal cancer referred to Imam Khomeini Hospital in Sari, and 100 controls without gastrointestinal symptoms who were also referred to the hospital. Participants were randomly selected based on inclusion and exclusion criteria, considering factors such as age, gender, and ethnicity. Data from each participant were collected through personal interviews using designed questionnaires. Results: The results showed no significant difference between the two groups in terms of gender (P=0.084). Although the average body mass index (BMI) of the patients was higher than that of the control group (26.64±4.01 kg/m² in the control group and 27.99±6.48 kg/m² in the case group), the difference was not statistically significant. Overall, there was no significant difference between the two groups in the prevalence of underlying diseases. A history of drug use revealed that patients used more folic acid, vitamin D, and antihypertensive medications. On the other hand, there was no significant difference in cigarette, hookah, or opium consumption between the two groups. However, the results indicated that the control group engaged in significantly more physical activity, and patients' ability to walk long distances was significantly lower compared to non-patients. In terms of diet, patients consumed more red meat, chicken, fish, and processed foods than the control group. Additionally, the consumption of vegetables—such as lettuce, fresh vegetables, and onions—was lower in patients compared to the control group. Conclusion: A family history of cancer, underlying conditions like hypertension and hyperlipidemia, a high body mass index, low physical activity, high intake of animal proteins, and low intake of vegetables were identified as risk factors for CRC in this study. Therefore, promoting healthier lifestyles, improving dietary habits, and encouraging physical activity should be priorities for health policymakers. Screening individuals with a family history of cancer could also help reduce the burden of colorectal cancer.